Concomitantly Diagnosed Disseminated Infection and Hairy Cell Leukemia With Review of Pathophysiology - Daniel J. Stanton MD; Nadia Z. Quadri MS; Melinda B. Tanabe MD, MSc (SAGE Publishing, 2024)
The association between Hairy Cell Leukemia (HCL) and non-tuberculous mycobacterial infections (NTMs) is well described, most notably Mycobacterium kansasii . The exact pathophysiology is not known. We report a case of a 31-year-old male with concomitantly diagnosed HCL and disseminated M kansasii infection who presented with rash, pancytopenia, and bulky axillary lymphadenopathy. The M kansasii was initially diagnosed through use of cell-free DNA detection and confirmed by bone marrow and lymph node cultures. Hairy Cell Leukemia was diagnosed with peripheral flow cytometry and confirmed via the same bone marrow sample. His HCL was put into remission with a single course of cladribine and rituximab chemotherapy; however, his M kansasii infection persisted for 6 months despite aggressive antimicrobial and surgical therapy. It was finally controlled using high-dose rifampin in combination with azithromycin and ethambutol. This case highlights the known link between HCL and M kansasii. Furthermore, it hints at potential causes beyond chemotherapy-induced immunocompromise. Notable possibilities include HCL cells acting as sanctuary sites for M kansasii to evade the immune system, and subclinical M kansasii infections causing NLRP3 inflammasome overactivation to trigger the oncogenic transformation to HCL. More research into the pathophysiologic link between HCL and M kansasii infections would allow for more effective prevention, diagnosis, and treatment of these severe atypical infections which are the major cause of morbidity in the cladribine era of HCL treatment.